2021
DOI: 10.31000/jhr.v9i2.4570
|View full text |Cite
|
Sign up to set email alerts
|

Position and Protection of Association Rights Security Unit in Human Rights Perspective According to the Basic State Law of the Republic of Indonesia Year 1945

Abstract: The rights and obligations in the world of labor have been regulated in the labor law, including the right of association which must be given to every worker to associate as stated in Law Number 21 of 2000 concerning Trade Unions / Labor Unions Article 28 and Article 43. In addition, problems arise when the Indonesian National Police Headquarters on behalf of the Indonesian National Police Chief through the Head of the Security Maintenance Agency issues Circular Letter Number; B/194/I/201/Baharkam concerning: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The results showed that both journalists and broadcasters should meet criteria such as having a good attitude, being militant, staying up-todate, having insights into music, being social media savvy, and being skilled in broadcasting and mastering broadcasting equipment. Additionally, Candra and Azmi (2021) conducted research on the skills of news anchor Imam Priyono in presenting "Indonesia Hari Ini" news on TVRI. However, none of these studies specifically examined the qualifications of news anchors for the Yogyawarta broadcast.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that both journalists and broadcasters should meet criteria such as having a good attitude, being militant, staying up-todate, having insights into music, being social media savvy, and being skilled in broadcasting and mastering broadcasting equipment. Additionally, Candra and Azmi (2021) conducted research on the skills of news anchor Imam Priyono in presenting "Indonesia Hari Ini" news on TVRI. However, none of these studies specifically examined the qualifications of news anchors for the Yogyawarta broadcast.…”
Section: Introductionmentioning
confidence: 99%